212 Oil spillage effects on health and safety among the local communities – experience from Bangladesh. (1st September 2016) - Hossain, Shafkat; Abdullah, Abu Sayeed; Hossain, Jahangir; Rahman, Aminur; Biswas, Animesh
Abstract : Background: on 9 th December 2014 an oil tanker collided with a cargo vessel at Sundarban, the largest mangrove forest in the world. About 350, 000 litres of furnace oil spilled into the Shela river. No major oil clean-up was in placed due to lack of equipments and experiences. However, most of the local people including children came to the place without any safety measures to collect oil so that they could sell it later. Methods: Qualitative method was used to explore the situation. IDI, FGD, observation technique and relevant daily national and international newspapers were reviewed to collect the information. Results: The disaster affected both on health and safety of the community. Primarily local people, who do not have any previous experience, were involved to collect the oil from the river and government showed interest to procure the furnace oil at a fix rate. This lead local community to start collecting oil and later on faced various health problems like diarrhoea, skin diseases, abdominal pain and headache etc. A child drowning case was found due to collecting oil. Though 7-year old kid was rescued he suffered from diarrhoea for four days. To get the better quality of oil community people boiled the oil so that water evaporated and quality of it became better. Females were involved in boiling oil and they faced severe headache, irritation on eyes and nose and vomiting tendency. Conclusion: Disaster preparedness is essential for any country like Bangladesh. Government should take necessary initiative on awareness and safety before involving local community in any disaster management especially dealing with chemicals2.Community people's safety should be the priority to avoid or reduce health effects.